(untitled) (PANGEEA, 2025)
The Getic area deposits. Given the current trend in metallic deposits research, namely to relate aspects of the genesis of mineralization in the tectonic evolution of the area by developments in global tectonics, the paper tries to apply this principle of mineralization in the Getic Domain of Southern Carpathians. This area has been strongly influenced by the existence of two microtectonical plates that supports the two areas of Southern Carpathians, respectively Getic area and Danubian area, developments in the framework of a collision cycle convergence-divergence type with major implications both in terms of genesis, as and the current spatial distribution of mineralization.